Meta-Analysis of Scientific Papers on effects of Motor Skills in the Basketball Published in the Journal Sport Mont from 2006 to 2018 - Ivan Vasiljevic (Journal of Anthropology of Sport and Physical Education)
The main objective of this research was to be done meta-analysis of original scientifi c papers published in the journal Sports Mont from 2006 to 2018, who determined the level of motor and situational-motor abilities in basketball players of diff erent ages. In this paper, a meta analysis of 6 papers in the fi eld of motor skills in basketball was conducted. On the basis of the parameters received in said original published scientifi c papers, it can be concluded that both the base and situational-motor abilities of primary importance for the identifi cation and characterization of young players, and by analogy, and the specialization of basketball game. It is necessary to monitor and apply the achievements of modern sports science, and thus the specifi c diagnosis of training young athletes. Motor diagnostics in sport is a fundamental science which is the initiator of top results every successful sports team should use at least some sort of diagnostic tools for testing and evaluation of athletes and to create training process